(3JSdjI GdMRjf HabO GdCMHGH hGdHfjfs - (3YHO Gddg Hf eMeO QVG GdMSjfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi bgQ YHGOg HGdehJ hGdafGA hJaQO HGdYR hGdHbGA hGHJdi YHGOg HGdCeQGV s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hCNQkG hXGgQkG hHGWfkG hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(129) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs